Likt og ulikt - vraking av saltfisk i Norge og Spania - Nøstvold, Bjørg Helen; Hansen, Kristin Beate; Joensen, Sjúrður; Østli, Jens; Esaiassen, Margrethe (Nofima, 2021)
Source at https://okonomiskfiskeriforskning.no/likt-og-ulikt-vraking-av-saltvisk-i-norge-og-spania/ I dette arbeidet er det undersøkt om kvaliteten på saltfisk vurderes likt av norske saltfiskprodusenter og spanske importører. Det ble gjennomført spørreundersøkelse og intervjuer, samt praktisk kvalitetsvurdering av saltfisk. Både spørreundersøkelsen og kvalitetsvurderingen viste at de spanske kjøperne var strengere på kriteriene for å klassifisere fisken som primera enn de norske produsentene. Det fremkom også noen forskjeller i vektingen av ulike typer enkeltfeil mellom produsenter og kjøpere. I 60 % av kvalitetsvurderingene fra de norske vrakerne ble fiskene markert til å være av primera handelskvalitet, mens de spanske kvalitetsvurderingene markerte i underkant av 40 % til denne kvalitetsklassen. Norway was previously market leader in saltfish of cod to Spain, but in the last decades Iceland have had this position and sells larger quantities of salted fish at a higher price per kilo than Norway. It seems that Icelandic producers have adjusted the products and quality grading more to the quality characteristics demanded by the Spanish market than Norwegian producers do. In order to explore whether Norwegian and Spanish quality assessors emphasize quality parameters differently when grading saltfish, a survey and an experimental quality assessment of the same batches of fish were conducted. According to the survey, the Spanish respondents rated most of the quality parameters as more important than the Norwegians did. In the quality assessments, the Spanish experts were stricter regarding which fish to be classified as superior quality (primera). There were also differences in the quality defects reported by the experts.